A Short-Chain Hydrophilic Ligand for the Preparation of Cu/AgNMs - Chen, Jie (Langmuir : the ACS journal of surfaces and colloids, 2025)
Many innovations have been made in the morphology and preparation methods of copper-silver core-shell nanomaterials (CuAgNMs). The most commonly used method for preparing Cu@AgNMs is to perform a replacement reaction by adding a complexing agent, but there is no universally accepted method to select a complexing agent. This study found that the best complexing agent for preparing Cu@AgNMs is a short-chain complexing agent containing hydrophilic groups through the role of different complexing agents in the synthesis of the material, and the higher the stability of the short-chain hydrophilic complexing agent, the better the integrity of the resulting silver layer. This study clarifies the mechanism of different complexing agents in the synthesis of Cu@AgNSs, provides a reliable reference for the convenient preparation of Cu@AgNMs, and helps us to understand the influence of complexing agents on the silvering effect of the replacement process, thereby promoting the widespread application of a complex-replacement technology